Advancements in the co-formulation of biologic therapeutics (2020)
Biologic therapeutics are the medicines of the future and are destined to transform the approaches by which the causes and symptoms of diseases are cured and alleviated. These approaches will be accelerated through the development of novel strategies that target multiple pharmacologically active sites using a combination of different biologics, or mixtures of biologics and small molecule therapeutics. However, for this potential to be realised, advancements in co-formulation strategies for biologic therapeutics must be established. This review describes the current and emerging developments within this field and highlights the challenges and potential solutions, that will pavethe-way towards their clinical translation.